SCIENCE AND EDUCATION IN UZBEKISTAN - Mirzaev Axad (Galaxy International Interdisciplinary Research Journal, 2021)
If today’s innovative technologies are successfully applied in science and education, there is no doubt that the new generation will learn from this world experience and the future of our country will be bright.